IMPLEMENTASI METODE FIRST COME FIRST SERVED PADA PLATFORM RESERVASI LAPANGAN BADMINTON BERBASIS MOBILE - Uro Abdulrohim; Dayanni Vera Versanika; Chandra Dirgantara (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2022)
Many badminton court rental service places still use a manual system, which only serves their customers by telephone or online conversation applications such as Whatsapp, so it is difficult to manage order data if there are many orders. The First Come First Served algorithm or commonly abbreviated (FCFS) is a calculation method based on the data that is inputted first, then the data is processed first. Usually the First Come First Served (FCFS) algorithm is used specifically for queuing systems because the First Come First Served algorithm because it is based on order is very suitable for systems that require systematic queuing. The design of this system uses the Extreme Programming method. From this research, it can produce an online reservation reservation system that can make it easier for customers to rent the field and make it easier for managers to promote the field by implementing the First Come Fist Served method.